IMPLEMENTASI PSIKOTERAPI PENANGGULANGAN STRESS DAN DEPRESI PADA PASIEN DI RUMAH SAKIT JIWA MADANI PALU - Thalib Thalib; Naima Naima (ISTIQRA, 2016)
Counseling and psychotherapy is one of the services providing assistance to people or individuals who have a problem of life, both individual with his own problems, problems of individuals with a family environment, and problems of the individual with the social environment. Another thing is many individuals who experience a spiritual problem. The latter is a problem experienced by an individual with his Lord, as an example: many individuals who are unable to hold a vertical relationship with God. In this context many individuals are difficult to bring fear, obey, and a sense that God is always watching the actions and behavior of each individual, thus impacting the feeling lazy and reluctant to worship, and the difficulty to abandon acts prohibited and disowned by his Lord, Allah SWT. From the description of the problems have, consequently there are the circumstances and conditions of negative psychological, such as stress and depression, if individuals do not have the endurance mentally and spiritually strong and tough, faith is weak, then it is very fragile and easily affected by the state of stress and depression. Individuals who experience these circumstances (stress and depression) is necessary and requires assistance psychologically and spiritually so that individual back stable mentally and spiritually. Therefore, the reality shows that many individuals who experience problems can solved and enlightened of the problem after the therapy at the Madani Mental Hospital. In this context, the study done